Analisis Beban Kerja Pekerja Wanita di Industri Manufaktur Kota Batam - Nofriani Fajrah; Sri Zetli (LPPM Universitas Putera Batam, 2023)
The manufacturing industry in Batam City is increasingly developing with the supporting factor being the availability of both female and male workers. The role of female workers in the Batam City manufacturing industry is quite significant, because female workers are chosen because of their thoroughness and discipline. The impact of this reason is that female workers have no restrictions and control over workload for female workers. This research aims to analyze the workload of female workers in the Batam City manufacturing industry. This research was conducted using descriptive analysis methods. The population of this research is female manufacturing industry workers in Batam City. Based on the results, it is known that the average pulse rate before work is 81.53, while after work it is 104.82. This shows an increase in heart rate after work, which indicates a significant increase in physical activity. This also shows that female workers in the manufacturing industry experience an increase in physical workload during work. Based on these data, it can be concluded that female workers in the manufacturing industry experience quite a high mental workload. The mental workload dimensions including MD, PD, TD, OP, EF, and FR show an average number above 70, which indicates a significant level of mental workload. Based on this research, it can provide implications for policy formulation regarding the management of female workers in the manufacturing industry in Batam City in particular and in Indonesia in general.